Modeling Climate and Hydropower Influences on the Movement Decisions of an Anadromous Species - Markus A. Min; Rebecca A. Buchanan; Mark D. Scheuerell (Global Change Biology, 2025)
In large river basins, migratory fish populations are threatened by the combination of hydropower and climate change. With river temperatures rising and hydropower development increasing globally, the longstanding monitoring programs for threatened Pacific salmon populations in the Columbia River Basin present an opportunity to study these impacts over extended time scales. We fit a statistical model to 20 years of PIT‐tagging data to jointly model the effects of temperature and dam operations (spill management) on the movement of Steelhead (anadromous Oncorhynchus mykiss ) during their adult pre‐spawn migration. We modeled the relationship between these factors and behaviors that pose mortality risks, including natal tributary overshoot (ascending a dam upstream of a natal tributary) and non‐natal tributary use. We then used the posterior distributions of model‐estimated parameters to predict the homing success of fish to natal tributaries under different climate and hydropower scenarios. Across the populations in our study, movement decisions were consistently thermally influenced, with temperature having a negative relationship with natal homing and a positive relationship with both natal tributary overshoot and non‐natal tributary use. Another consistent finding across the populations in our study was that higher overshoot rates were associated with lower homing rates. Despite data limitations associated with the PIT‐tag array network, we found evidence for population‐specific benefits of winter spill on natal homing success, which is currently being implemented to assist the downstream migration of overshooting Steelhead. We demonstrate how integrating the effects of climate and hydropower management actions with movement ecology provides powerful insights into how species may respond to future scenarios. In our case study, we found that pre‐spawn mortality of Steelhead is likely to increase with future climate change due to temperature‐driven interactions with the hydrosystem, but there is potential for hydropower managers to partially offset these impacts.

Declining Marine Survival of Steelhead Trout Linked to Climate and Ecosystem Change - Jan Ohlberger; Eric R. Buhle; Thomas W. Buehrens; Neala W. Kendall; Toby Harbison; Andrew M. Claiborne; James P. Losee; Jennifer Whitney; Mark D. Scheuerell (Fish and Fisheries, 2025)
Species with complex life cycles, such as anadromous fish that perform spawning migrations between freshwater and the ocean, may be particularly sensitive to global change because freshwater and marine habitats experience distinct shifts in climate and ecosystem dynamics. Abundances of wild steelhead trout ( Oncorhynchus mykiss ) have declined across most of their range over the past 40–50 years. We examined whether declines in steelhead survival can be linked to changing climate conditions and species interactions. A novel hierarchical integrated population model that accounts for the species' complex life history was fitted to data from multiple wild steelhead populations on the Washington coast, U.S.A. The model estimates recruitment residuals and kelt survival rates as time‐varying processes, which reflect annual variation in survival before and after first maturation. We found that survival rates of immature steelhead (recruits) and adult steelhead (kelts) have declined over time and that survival trends across populations were strongly associated with climate and ecosystem change, specifically summer sea surface temperature and pink salmon abundance in the North Pacific Ocean, the NPGO index and river flows. Including these drivers in the model reduced unexplained annual variation in shared recruitment and kelt survival anomalies and largely accounted for their negative long‐term trends. Our findings provide evidence that rising temperatures and increased interspecific competition at sea have contributed to declines in steelhead survival over the last five decades. Considering projected warming and high pink salmon abundances in the ocean, steelhead will likely continue to experience low marine survival rates.

Stable isotopes reveal intertidal fish and crabs use bivalve farms as foraging habitat in Puget Sound, Washington - Karl B. Veggerby; Mark D. Scheuerell; Beth L. Sanderson; Peter M. Kiffney (Frontiers in Marine Science, 2024)
Bivalves such as oysters and clams have been farmed in intertidal zones across the Puget Sound region of the Salish Sea for thousands of years. The variety of gear types used on bivalve farms creates complex vertical structure and attachment points for aquatic epiphytes and invertebrates which increases habitat structural complexity, but may alter eelgrass cover in areas where bivalve farms and eelgrass meadows overlap. Eelgrass meadows are highly productive and ecologically foundational nearshore habitats that provide valuable ecosystem services including the provision of nursery, refuge, and foraging habitat. Aquaculture has been a key feature of the environment in the Puget Sound for millennia, however, little is known about how well aquaculture practices are integrated into the system, and what services they provide to mobile species assemblages relative to unfarmed eelgrass meadows. We used stable isotope mixing models to estimate, for several species of nearshore fish and crab in two areas of North Puget Sound, Washington, the percent diet originating from either a natural bottom habitat (eelgrass meadows), farm habitat (oyster farms), or pelagic planktonic sources. Our results indicate that several species of nearshore fish such as surf perch and staghorn sculpin derive a significant proportion of their diets from farm areas, while crabs derive most of their diets from eelgrass habitat, and stickleback derive a significant proportion of their diets from planktonic sources. The results indicate that foraging habitat uses are species specific, and that several species that spatially overlap bivalve farms obtained a large percentage of their diets from adjacent bivalve farm habitat.

Multi-Scale Temporal Patterns in Stream Biogeochemistry Indicate Linked Permafrost and Ecological Dynamics of Boreal Catchments - Alex J. Webster; Thomas A. Douglas; Peter Regier; Mark D. Scheuerell; Tamara K. Harms (Ecosystems, 2022)

Long‐term perspectives in aquatic research - Stephanie E. Hampton; Mark D. Scheuerell; Matthew J. Church; John M. Melack (Limnology and Oceanography, 2019)
Long‐term research provides a unique perspective on environmental processes, dynamics of populations and communities of organisms, and emergent properties of ecosystems. Many key ecological relationships can be obscured in short term studies by common features such as time lags, natural variability, nonlinear relationships, interactive drivers, or relatively slow processes. Aquatic ecosystems have yielded major scientific discoveries through long‐term research, through both observational and experimental studies. These research results have ranged from the detection of multi‐decadal climate oscillation effects on ecosystems to finer‐scale understanding of the trophic and biogeochemical pathways through which nutrient pollution affects water quality. In this special issue of Limnology and Oceanography , the contributing authors demonstrate that—whether designed for the monitoring of managed natural resources, to answer fundamental scientific questions, or both—long‐term research enables researchers to move far beyond their initial questions as unexpected dynamics are revealed over time. With the widespread maturation of long‐term data sets and rapid emergence of new technologies that enhance research capabilities, opportunities for synthesizing knowledge are now creating unprecedented opportunity for scientific discovery that builds on this legacy of long‐term aquatic research.

Applying spatiotemporal models to monitoring data to quantify fish population responses to the Deepwater Horizon oil spill in the Gulf of Mexico - Eric J. Ward; Kiva L. Oken; Kenneth A. Rose; Shaye Sable; Katherine Watkins; Elizabeth E. Holmes; Mark D. Scheuerell (Environmental Monitoring and Assessment, 2018)

Joint dynamic species distribution models: a tool for community ordination and spatio‐temporal monitoring - James T. Thorson; James N. Ianelli; Elise A. Larsen; Leslie Ries; Mark D. Scheuerell; Cody Szuwalski; Elise F. Zipkin (Global Ecology and Biogeography, 2016)
Aim Spatial analysis of the distribution and density of species is of continuing interest within theoretical and applied ecology. Species distribution models (SDMs) are being increasingly used to analyse count, presence–absence and presence‐only data sets. There is a growing literature on dynamic SDMs (which incorporate temporal variation in species distribution), joint SDMs (which simultaneously analyse the correlated distribution of multiple species) and geostatistical models (which account for similarity between nearby sites caused by unobserved covariates). However, no previous study has combined all three attributes within a single framework. Innovation We develop spatial dynamic factor analysis for use as a ‘joint, dynamic SDM’ (JDSDM), which uses geostatistical methods to account for spatial similarity when estimating one or more ‘factors’. Each factor evolves over time following a density‐dependent (Gompertz) process, and the log‐density of each species is approximated as a linear combination of different factors. We demonstrate a JDSDM using two multispecies case studies (an annual survey of bottom‐associated species in the Bering Sea and a seasonal survey of butterfly density in the continental USA), and also provide our code publicly as an R package. Main conclusions Case study applications show that that JDSDMs can be used for species ordination, i.e. showing that dynamics for butterfly species within the same genus are significantly more correlated than for species from different genera. We also demonstrate how JDSDMs can rapidly identify dominant patterns in community dynamics, including the decline and recovery of several Bering Sea fishes since 2008, and the ‘flight curves’ typical of early or late‐emerging butterflies. We conclude by suggesting future research that could incorporate phylogenetic relatedness or functional similarity, and propose that our approach could be used to monitor community dynamics at large spatial and temporal scales.

Demographic modeling of citizen science data informs habitat preferences and population dynamics of recovering fishes - James T. Thorson; Mark D. Scheuerell; Brice X. Semmens; Christy V. Pattengill-Semmens (Ecology, 2014)
Managing natural populations and communities requires detailed information regarding demographic processes at large spatial and temporal scales. This combination is challenging for both traditional scientific surveys, which often operate at localized scales, and recent citizen science designs, which often provide data with few auxiliary information (i.e., no information about individual age or condition). We therefore combine citizen science data at large scales with the demographic resolution afforded by recently developed, site‐structured demographic models. We apply this approach to categorical data generated from citizen science representing species density of two managed reef fishes in the Gulf of Mexico, and use a modified Dail‐Madsen model to estimate demographic trends, habitat associations, and interannual variability in recruitment. This approach identifies strong preferences for artificial structure for the recovering Goliath grouper, while revealing little evidence of either habitat associations or trends in abundance for mutton snapper. Results are also contrasted with a typical generalized linear mixed‐model (GLMM) approach, using real‐world and simulated data, to demonstrate the importance of accounting for the statistical complexities implied by spatially structured citizen science data. We conclude by discussing the increasing potential for synthesizing demographic models and citizen science data, and the management benefits that can be accrued.

Influence of ocean and freshwater conditions on C olumbia R iver sockeye salmon Oncorhynchus nerka adult return rates - John G. Williams; Steven G. Smith; Jeffrey K. Fryer; Mark D. Scheuerell; William D. Muir; Tom A. Flagg; Richard W. Zabel; John W. Ferguson; Edmundo Casillas (Fisheries Oceanography, 2014)
In recent years, returns of adult sockeye salmon O ncorhynchus nerka to the C olumbia R iver B asin have reached numbers not observed since the 1950s. To understand factors related to these increased returns, we first looked for changes in freshwater production and survival of juvenile migrants. We then evaluated productivity changes by estimating smolt‐to‐adult return rates ( SAR ) for juvenile migration years 1985–2010. We found SAR varied between 0.2 and 23.5%, with the highest values coinciding with recent large adult returns. However, the largest adult return, in 2012, resulted not from increased survival, but from increased smolt production. We evaluated 19 different variables that could influence SAR s, representing different facets of freshwater and ocean conditions. We used model selection criteria based on small‐sample corrected AIC to evaluate the relative performance of all two‐ and three‐variable models. The model with A pril upwelling, P acific N orthwest I ndex ( PNI ) in the migration year, and PNI in the year before migration had 10 times the AIC c weight as the second‐best‐supported model, and R 2 = 0.82. The variables of A pril ocean upwelling and PNI in the migration year had high weights of 0.996 and 0.927, respectively, indicating they were by far the best of the candidate variables to explain variations in SAR . While our analyses were primarily correlative and limited by the type and amount of data currently available, changes in ocean conditions in the northern C alifornia Current system, as captured by April upwelling and PNI , appeared to play a large role in the variability of SAR .

Quantifying effects of abiotic and biotic drivers on community dynamics with multivariate autoregressive (MAR) models - Stephanie E. Hampton; Elizabeth E. Holmes; Lindsay P. Scheef; Mark D. Scheuerell; Stephen L. Katz; Daniel E. Pendleton; Eric J. Ward (Ecology, 2013)
Long‐term ecological data sets present opportunities for identifying drivers of community dynamics and quantifying their effects through time series analysis. Multivariate autoregressive (MAR) models are well known in many other disciplines, such as econometrics, but widespread adoption of MAR methods in ecology and natural resource management has been much slower despite some widely cited ecological examples. Here we review previous ecological applications of MAR models and highlight their ability to identify abiotic and biotic drivers of population dynamics, as well as community‐level stability metrics, from long‐term empirical observations. Thus far, MAR models have been used mainly with data from freshwater plankton communities; we examine the obstacles that may be hindering adoption in other systems and suggest practical modifications that will improve MAR models for broader application. Many of these modifications are already well known in other fields in which MAR models are common, although they are frequently described under different names. In an effort to make MAR models more accessible to ecologists, we include a worked example using recently developed R packages (MAR1 and MARSS), freely available and open‐access software.

Interacting Effects of Translocation, Artificial Propagation, and Environmental Conditions on the Marine Survival of Chinook Salmon from the Columbia River, Washington, U.S.A. - KIRSTIN K. HOLSMAN; MARK D. SCHEUERELL; ERIC BUHLE; ROBERT EMMETT (Conservation Biology, 2012)
Captive rearing and translocation are often used concurrently for species conservation, yet the effects of these practices can interact and lead to unintended outcomes that may undermine species’ recovery efforts. Controls in translocation or artificial‐propagation programs are uncommon; thus, there have been few studies on the interacting effects of these actions and environmental conditions on survival. The Columbia River basin, which drains 668,000 km 2 of the western United States and Canada, has an extensive network of hydroelectric and other dams, which impede and slow migration of anadromous Pacific salmon ( Oncorhynchus spp. ) and can increase mortality rates. To mitigate for hydrosystem‐induced mortality during juvenile downriver migration, tens of millions of hatchery fish are released each year and a subset of wild‐ and hatchery‐origin juveniles are translocated downstream beyond the hydropower system. We considered how the results of these practices interact with marine environmental conditions to affect the marine survival of Chinook salmon ( O. tshawytscha ). We analyzed data from more than 1 million individually tagged fish from 1998 through 2006 to evaluate the probability of an individual fish returning as an adult relative to its rearing (hatchery vs. wild) and translocation histories (translocated vs. in‐river migrating fish that traveled downriver through the hydropower system) and a suite of environmental variables. Except during select periods of very low river flow, marine survival of wild translocated fish was approximately two‐thirds less than survival of wild in‐river migrating fish. For hatchery fish, however, survival was roughly two times higher for translocated fish than for in‐river migrants. Competition and predator aggregation negatively affected marine survival, and the magnitude of survival depended on rearing and translocation histories and biological and physical conditions encountered during their first few weeks of residence in the ocean. Our results highlight the importance of considering the interacting effects of translocation, artificial propagation, and environmental variables on the long‐term viability of species.

Climate shifts the interaction web of a marine plankton community - Tessa B. Francis; Mark D. Scheuerell; Richard D. Brodeur; Phillip S. Levin; James J. Ruzicka; Nick Tolimieri; William T. Peterson (Global Change Biology, 2012)
Climatic effects in the ocean at the community level are poorly described, yet accurate predictions about ecosystem responses to changing environmental conditions rely on understanding biotic responses in a food‐web context to support knowledge about direct biotic responses to the physical environment. Here we conduct time‐series analyses with multivariate autoregressive ( MAR ) models of marine zooplankton abundance in the Northern California Current from 1996 to 2009 to determine the influence of climate variables on zooplankton community interactions. Autoregressive models showed different community interactions during warm vs. cool ocean climate conditions. Negative ecological interactions among zooplankton groups characterized the major warm phase during the time series, whereas during the major cool phase, ocean transport largely structured zooplankton communities. Local environmental conditions (sea temperature) and large‐scale climate indices (El Niño/Southern Oscillation) were associated with changes in zooplankton abundance across the full time series. Secondary environmental correlates of zooplankton abundance varied with ocean climate phase, with most support during the warm phase for upwelling as a covariate, and most support during the cool phase for salinity. Through simultaneous quantitation of community interactions and environmental covariates, we show that marine zooplankton community structure varies with climate, suggesting that predictions about ecosystem responses to future climate scenarios in the Northern California Current should include potential changes to the base of the pelagic food.

Evolutionary responses by native species to major anthropogenic changes to their ecosystems: Pacific salmon in the Columbia River hydropower system - ROBIN S. WAPLES; RICHARD W. ZABEL; MARK D. SCHEUERELL; BETH L. SANDERSON (Molecular Ecology, 2008)
The human footprint is now large in all the Earth's ecosystems, and construction of large dams in major river basins is among the anthropogenic changes that have had the most profound ecological consequences, particularly for migratory fishes. In the Columbia River basin of the western USA, considerable effort has been directed toward evaluating demographic effects of dams, yet little attention has been paid to evolutionary responses of migratory salmon to altered selective regimes. Here we make a first attempt to address this information gap. Transformation of the free‐flowing Columbia River into a series of slack‐water reservoirs has relaxed selection for adults capable of migrating long distances upstream against strong flows; conditions now favour fish capable of migrating through lakes and finding and navigating fish ladders. Juveniles must now be capable of surviving passage through multiple dams or collection and transportation around the dams. River flow patterns deliver some groups of juvenile salmon to the estuary later than is optimal for ocean survival, but countervailing selective pressures might constrain an evolutionary response toward earlier migration timing. Dams have increased the cost of migration, which reduces energy available for sexual selection and favours a nonmigratory life history. Reservoirs are a benign environment for many non‐native species that are competitors with or predators on salmon, and evolutionary responses are likely (but undocumented). More research is needed to tease apart the relative importance of evolutionary vs. plastic responses of salmon to these environmental changes; this research is logistically challenging for species with life histories like Pacific salmon, but results should substantially improve our understanding of key processes. If the Columbia River is ever returned to a quasinatural, free‐flowing state, remaining populations might face a Darwinian debt (and temporarily reduced fitness) as they struggle to re‐evolve historical adaptations.

The Interplay between Climate Variability and Density Dependence in the Population Viability of Chinook Salmon - RICHARD W. ZABEL; MARK D. SCHEUERELL; MICHELLE M. McCLURE; JOHN G. WILLIAMS (Conservation Biology, 2006)
The viability of populations is influenced by driving forces such as density dependence and climate variability, but most population viability analyses (PVAs) ignore these factors because of data limitations. Additionally, simplified PVAs produce limited measures of population viability such as annual population growth rate (λ) or extinction risk. Here we developed a “mechanistic” PVA of threatened Chinook salmon ( Oncorhynchus tshawytscha ) in which, based on 40 years of detailed data, we related freshwater recruitment of juveniles to density of spawners, and third‐year survival in the ocean to monthly indices of broad‐scale ocean and climate conditions. Including climate variability in the model produced important effects: estimated population viability was very sensitive to assumptions of future climate conditions and the autocorrelation contained in the climate signal increased mean population abundance while increasing probability of quasi extinction. Because of the presence of density dependence in the model, however, we could not distinguish among alternative climate scenarios through mean λ values, emphasizing the importance of considering multiple measures to elucidate population viability. Our sensitivity analyses demonstrated that the importance of particular parameters varied across models and depended on which viability measure was the response variable. The density‐dependent parameter associated with freshwater recruitment was consistently the most important, regardless of viability measure, suggesting that increasing juvenile carrying capacity is important for recovery.

Forecasting climate‐induced changes in the survival of Snake River spring/summer Chinook salmon ( Oncorhynchus tshawytscha ) - MARK D. SCHEUERELL; JOHN G. WILLIAMS (Fisheries Oceanography, 2005)
Effective conservation and management of natural resources requires accurate predictions of ecosystem responses to future climate change, but environmental science has largely failed to produce these reliable forecasts. The future response of Pacific salmon ( Oncorhynchus spp.) to a changing environment and continued anthropogenic disturbance is of particular interest to the public because of their high economic, social, and cultural value. While numerous retrospective analyses show a strong correlation between past changes in the ocean environment and salmon production within the north Pacific, these correlations rarely make good predictions. Using a Bayesian time‐series model to make successive 1‐yr‐ahead forecasts, we predicted changes in the ocean survival of Snake River spring/summer chinook salmon ( O. tshawytscha ) from indices of coastal ocean upwelling with a high degree of certainty ( R 2 = 0.71). Furthermore, another form of the dynamic times‐series model that used all of the available data indicated an even stronger coupling between smolt‐to‐adult survival and ocean upwelling in the spring and fall ( R 2 = 0.96). This suggests that management policies directed at conserving this threatened stock of salmon need to explicitly address the important role of the ocean in driving future salmon survival.

Disturbance of freshwater habitats by anadromous salmon in Alaska - Jonathan W. Moore; Daniel E. Schindler; Mark D. Scheuerell (Oecologia, 2004)

Changes in the Spatial Distribution of Fishes in Lakes Along a Residential Development Gradient - Mark D. Scheuerell; Daniel E. Schindler (Ecosystems, 2004)

Environmental and algal forcing of Daphnia production dynamics - Mark D. Scheuerell; Daniel E. Schindler; Arni H. Litt; W. T. Edmondson (Limnology and Oceanography, 2002)
Recent studies of lakes suggest that the relative availability of light and phosphorus in the mixed layer helps determine the quality of phytoplankton consumed by herbivorous zooplankton. In turn, increases in algal quality positively affect zooplankton growth and reproductive rates. However, these studies have concentrated on explaining variation among lakes over relatively short time periods and have not evaluated the temporal dynamics in the physical‐chemical forcing on zooplankton production. We investigated whether there were seasonal changes in the relationship between Daphnia fecundity and the physical‐chemical environment, algal community characteristics, and Daphnia length using dynamic linear models (DLM) to analyze a high‐resolution, 16‐yr time series from Lake Washington. We used two metrics to describe algal quality: the percentage of blue‐green algae and the light to total phosphorus (TP) ratio as an indirect metric for algal C: P. Chlorophyll a (Chl a) concentration and algal biovolume served as measures of algal quantity. As expected, both the light :TP ratio and the percentage of blue‐green algae had negative effects on Daphnia fecundity, and Chl a concentration and biovolume had positive effects on fecundity. However, we found a comparatively stronger effect of Daphnia length on fecundity, although it was negative and therefore opposite to expectation. In all cases, we observed strong seasonal differences in environmental effects, but no temporal change in the fundamental relationships between our indices of algal quantity and quality, allometry, and Daphnia reproduction. Our results support a hypothesis of physical‐chemical coupling to algal quality and zooplankton production but highlight the importance of temporal variation in this forcing.